Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Di Bursa Efek Indonesia (BEI) - Abila Riris Zurmawati; Muazaroh Muazaroh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of financial performance on firm value with dividend policy as a moderating variable. In this study the authors used a quantitative approach, and based on the type of data is secondary data. The analysis used is multiple linear regression and MRA (Moderated Regression Analysis) using SPSS software. the variables used, namely the measurement of influencing factors (independent variables) are financial performance, namely liquidity, financial leverage and profitability. The factors that are affected (dependent variable) are firm values (Tobin`s Q). The moderating variable which is the independent variable as well as the dependent variable is dividend policy. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX). The results of this study are that the variable liquidity on firm value does not have a positive influence. While the results of the research on dividend policy as a moderating variable on liquidity on firm value, indicate that liquidity was not tested for moderation because previously it had obtained negative results, namely it did not have a significant effect even though a moderation test was carried out with the dividend policy variable. leverage has a positive effect on firm value and the results of dividend policy research as a moderating variable on leverage on firm value show that leverage has no effect on firm value, profitability research on firm value shows that profitability has a positive effect, results of dividend policy research as a moderating variable on profitability on firm value, indicating that profitability has no effect on firm value. Keywords: Financial Performance, Firm Value, Dividend Policy, Manufacturing